RATINGS OF INVESTMENT APPEAL OF REGIONS OF RUSSIA AS A TOOL OF ASSESSMENT OF REGION MANAGEMENT EFFICIENCY - Bondarenko, Irina (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2016)
One of a determinant of region management efficiency is sustainable economic development that is based on active attraction of investments and business development in the region. Thus, appeal of the region for investments can used as an indicator of authorities’ efficiency in the region. The article considers possibility of application of independent ratings of regions for an assessment of region management efficiency.